Abiotic Stress in Plants - Adaptations to Climate Change 2023
DOI: 10.5772/intechopen.110201
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Abiotic Stress Tolerance in Plants with the Application of Nanoparticles

Abstract: Plants are under the threat of climatic changes and there is a reduction in productivity and deterioration in quality. The application of nanoparticles is one of the recent approaches to improve plant yield and quality traits. A number of nanoparticles, such as zinc nanoparticles (ZnO NPs), iron nanoparticles (Fe2O3 NPs), silicon nanoparticles (SiO2 NPs), cerium nanoparticles (CeO2 NPs), silver nanoparticles (Ag NPs), titanium dioxide nanoparticles (TiO2 NPs), and carbon nanoparticles (C NPs), have been report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…The performance of plants are dependent on various processes such as biochemical, physiological and anatomical mechanisms, and these functions are connected to the internal anatomy (Rasheed et al, 2022). The application of SiNPs resulted in membrane stability, enhanced anatomical parameters, and nutrient status (Figure 2) (Nawaz et al, 2023). In a study conducted by Adress et al (2022) on wheat, it was observed that foliar application of SiNPs leads to increased Si content in both roots or shoots.…”
Section: Sinps Enhance Morpho-histological Attributesmentioning
confidence: 99%
“…The performance of plants are dependent on various processes such as biochemical, physiological and anatomical mechanisms, and these functions are connected to the internal anatomy (Rasheed et al, 2022). The application of SiNPs resulted in membrane stability, enhanced anatomical parameters, and nutrient status (Figure 2) (Nawaz et al, 2023). In a study conducted by Adress et al (2022) on wheat, it was observed that foliar application of SiNPs leads to increased Si content in both roots or shoots.…”
Section: Sinps Enhance Morpho-histological Attributesmentioning
confidence: 99%